AB0174 Relationship of matrix metalloproteinase-3 concentration with clinical, laboratory and ultrasonographic markers of rheumatoid arthritis activity. (23rd January 2014) - Flicinski, J.; Kubis, M.; Brzezinski, M.; Kaszuba, M.; Butkiewicz, F.; Izbicki, J.; Lopinski, H.; Fischer, K.; Brzosko, M.
Abstract : Background: Rheumatoid arthritis (RA) is a disease of the connective tissue, in the course of which the occurrence of symmetrical peripheral joints arthritis is the main symptom. It may lead to irreversible destruction of musculoskeletal system. Matrix metalloproteinase-3 (MMP-3) is a proteolytic enzyme which participates in the destruction of cartilage and bone, also in the course of active RA. As such it might be a sensitive marker of bone and cartilage tissue destruction also in an early stage of the disease. It could be also helpful in identifying patients at high risk of the osteolytic lesions occurrence. Objectives: The aim of this study was to assess the relationship of MMP-3 concentration with already recognized clinical and laboratory markers of RA activity in order to evaluate its potential role in monitoring the RA activity. Methods: 34 consecutive patients with established RA from the outpatient clinic were qualified for the study (all meeting the 2010 EULAR/ACR criteria). All of them consented to the study. Each patient was evaluated for concentration of MMP-3 (Aesculis DF MMP-3) and CRP together with routine monitoring blood tests. They were also asked to evaluate their disease activity on VAS scale. Peripheral joints of were examined for presence of tenderness and effusion, and assessed using ultrasound. The ultrasonographic assessment included gray scale and power Doppler mode examinations of radiocarpal, midcarpal, distal radioulnar joints of both wrists, also metacarpophalangeal and metatarsophalangeal joints in 0 – 3 grading scales for synovitis. The 1-6. compartments of the wrists extensors were assessed for tenosynovitis. The ultrasonographer was blinded to the results of physical examination and laboratory tests of the patients. The Disease Activity Score 28 was calculated for every patient. There were 24 patients with increased concentration of MMP-3 (mean age 55, 1 yrs) who constituted the studied group while the ones with normal MMP-3 concentration created a control group (mean age 51, 1 yrs). Mann-Whitney test, Kruskal-Wallis test, χ2Pearson's test with Yates's correction and logistic regression model were performed for statistical evaluation of the results. Results: High concentration of MMP-3 was associated with joint swelling (p=0, 041), presence of extraarticular symptoms of RA (p=0, 034) and also with increased values of CRP (p=0, 038). The increased MMP-3 levels were also significantly related to abnormalities shown on ultrasonography of the wrists, i.e. synovial overgrowth of the wrist joints shown in gray scale ultrasonographic assessment (p=0, 019) and to active tenosynovitis (both in gray scale and in power Doppler mode) within any of the 6 compartments of wrist extensors (p=0, 017). Conclusions: The study demonstrated that MMP-3 levels are significantly associated with clinical, laboratory and also with ultrasonographic features of RA activity. High concentration of MMP-3 seems to reflect high activity of RA, so it might be considered as a reliable laboratory marker of the disease, what warrants further studies on bigger populations. Disclosure of Interest: None Declared